Prolactin secretion pattern among female flight attendants - Małgorzata Radowicka; Bronisława Pietrzak; Mirosław Wielgoś (International Journal of Occupational Medicine and Environmental Health, 2021)
Objectives Epidemiological observations indicate that female flight attendants are exposed to some reproductive and endocrine system disturbances. The aim of the study was to determine the incidence of hyperprolactinemia among female flight attendants, and to identify factors affecting the secretion of prolactin in female flight attendants working within 1 time zone as well as on long-distance flights.